Software Supply Chain Risk: Characterization, Measurement & Attenuation - Butler, Alexis (IEEE/ACM International Conference on Automated Software Engineering : [proceedings], 2024)
With the accelerating adoption of open source software, and an ever-growing body of case studies of security vulnerabilities being introduced by said open source software (Log4J arbitrary code execution, OpenSSH backdoor by way of XZ-utils, and the Polyfill CDN take over), the need for supply chain observability has become increasingly urgent. This need has been acknowledged by both industry and government, with calls to enforce the adoption of Software Bills of Materials (SBOMs).Current software security metrology efforts focus on individual packages within an ecosystem, with very little work exploring how security risk propagates through dependency networks. This research proposal sets out a number of research objectives and proposed approaches that when combined look to develop metrics that better align with the needs of software engineering practitioners, and further the understanding of the role of dependency networks in the propagation of risk within open source software.